Актуальні проблеми регулювання обліку трудової діяльності працівника - Чорноус, О. В.; Chornous, O. V.; ORCID: http://orcid.org/0000-0002-1475-7990 (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 4 (99). – С. 121-129, 2022)
Висвітлено окремі положення національного законодавства у сфері трудових відносин. Розглянуто основні аспекти впровадження електронної форми фіксації страхового стажу працівника. Проаналізовано Закон України «Про внесення змін до деяких законодавчих актів України щодо обліку трудової діяльності працівника в електронній формі» та інше актуальне законодавство з означеної проблематики. Увагу дослідження спрямовано на врегулювання теоретичних і практичних проблемних аспектів реформування інституту трудових книжок в умовах воєнного стану.

This article has analyzed the current labor legislation on recording of an employee’s labor activity. The study focuses on the settlement of theoretical and practical problematic aspects of the process of employment records digitalization, and on the non-infringement of employees’ and pensioners’ labor rights and as subjects of labor relations in this regard. The law stipulates that an employee’s work activity will be recorded in electronic form. In addition, it regulates the procedure for accumulating, processing and using this information to confirm the length of service and automatically grants pensions with the right to postpone retirement. The legislator envisages a gradual transition from paper to electronic employment records by 2025. Within this period, it is possible to use both versions of the existing or entered information about the employee’s work history from the state register. We believe that the purpose of introducing a digital analog of a paper employment record book was to improve the recording of Ukrainians’ labor activity, reduce paperwork and the associated risks of loss or damage to documents. It has been found that the provisions of the Law of Ukraine “On Amendments to Certain Legislative Acts of Ukraine on Electronic Employee Labor Records” have gaps in this regard which require further improvement and elaboration.

Отражены отдельные положения национального законодательства в сфере трудовых отношений. Рассмотрены основные аспекты внедрения электронной формы фиксации страхового стажа работника. Проанализирован Закон Украины «О внесении изменений в некоторые законодательные акты Украины об учете трудовой деятельности работника в электронной форме» и другое актуальное законодательство по данной проблематике. Внимание исследования направлено на урегулирование теоретических и практических проблемных аспектов реформирования института трудовых книжек в условиях военного положения.
Current issues of regulating on recording of the employee’s labor activities
Чорноус, О. В. Актуальні проблеми регулювання обліку трудової діяльності працівника / Олена Василівна Чорноус // Вісник Харківського національного університету внутрішніх справ. – 2022. – № 4 (99). – С. 121-129. - DOI: https://doi.org/10.32631/v.2022.4.10.
Чорноус, О. В. (2022) «Актуальні проблеми регулювання обліку трудової діяльності працівника», Вісник Харківського національного університету внутрішніх справ, 99(4), с. 121-129. doi: 10.32631/v.2022.4.10.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; трудові відносини; labor relations; трудовые отношения; трудова книжка; employment history; трудовая книжка; працівник; employee; работник; пенсіонер; pensioner; пенсионер; облік трудової діяльності; accounting of labor activity; учет трудовой деятельности; стаж роботи; work experience; стаж работы